D‐dimer is a predictor of clot resolution in patients with pulmonary thromboembolism: A retrospective cohort study. (28th February 2020) - An, Jun; Sun, Bo; Ji, Yingqun; Zhang, Zhonghe; Zhai, Zhenguo; Wang, Chen
Abstract: Background: This study assessed predictors of pulmonary thromboembolism (PE) resolution and their implications for clinical outcome. Method: A total of 150 patients with acute PE diagnosed by computed tomography pulmonary angiography (CTPA) were included. All patients received anticoagulant therapy for 3‐6 months and were followed‐up for at least 2 years. d ‐dimer levels in plasma were assayed at the first admission and during follow‐up. Results: The rate of CTPA‐confirmed PE resolution was 48.67% at 6 months, 68% at 12 months, and 78.67% at 24 months. Thirty‐nine patients had recurrent thrombosis after anticoagulation therapy was stopped, whereas 93 patients had complete resolution. The initial d ‐dimer level positively correlated with the pulmonary artery obstruction index (PAOI) ( r = 0.21; P = 0.015), but did not significantly differ between patients experiencing resolution or recurrence. In contrast, the follow‐up mean d ‐dimer level was significantly higher in the recurrent group ( P < 0.001), and this level was an independent risk factor for recurrent PE after the termination of anticoagulation treatment (OR 1.003, 95%CI 1.002 to 1.004; P < 0.001). Higher initial thromboembolic burden measured by PAOI was associated with residual thromboemboli ( P = 0.004) and recurrence ( P = 0.03), but was not an independent risk factor for either. Conclusions: Elevated d ‐dimer is an independent risk factor for PE recurrence. A higher initial thromboembolic burden may be associated with unresolved thromboemboli or recurrence.